Crisis Management: The Activities of Nurse Managers in Turkey - (:unkn) unknown (JANNETTI PUBLICATIONS, INC, 2011)
Crisis management is the process of preventing the organization from getting into a crisis and taking the organization out of the situation with minimum costs and losses in sudden crisis situation. A descriptive study design was used to determine the activities of nurse managers regarding crisis management. The most common type of crisis encountered at hospitals was natural disasters such as earthquakes. To cope with stress regarding crises, 71.6% of nurse managers stated they leave the resolution of crises to the top management, 64.7% noted they increase the number of the staff members, and 58.1% said they ignore crises. It was concluded nurse managers were partially prepared for crises or crisis management. Activities of nurse managers for more efficient crisis management in hospitals can be restructured according to the results and suggestions of the research. Crises can be coped with, turned into opportunities, and negative effects of crises can be minimized.